Collaborative Strategy between Cooperatives and Jeep Groups in Digital Marketing to Improve the Competitiveness of Rural Ecotourism and Jeep Groups in Digital Marketing to Improve the Competitiveness of Rural Ecotourism - Wisadirana, Darsono; Avina , Diyah Ayu Amalia; Sari, Qurnia Indah Permata; Sasmita , Ajeng Yuri Eka; Putera, Vildan Cresanda Hutama (Edumedia Solution, 2026)
Pamotan Village, Dampit Subdistrict, Malang Regency, East Java, is an area with promising ecotourism potential due to its rich natural resources, local culture, and stunning biodiversity. However, the potential of Dampit Village has not been optimally utilized by either the community or the village government. Therefore, the community service team encouraged collaboration between the Panorama Lereng Semeru cooperative and the Malang Willys Club Jeep group through the use of digital marketing technology. The methods used in this activity were Focus Group Discussions (FGDs) and training in the use of information technology and digital marketing for cooperative administrators, the Jeep group, and village residents. The results of this activity were the mapping of issues and activity plans between the cooperative administrators and the Jeep group regarding the development of ecotourism and the emergence of community understanding of the use of digital marketing technology to promote the ecotourism potential in their area. It can be concluded that this collaboration strategy is able to integrate natural potential, local culture, and digital technology to enhance the competitiveness of ecotourism. Through digital marketing training and creative content on social media such as Instagram, TikTok, and several other social media platforms, it is hoped that the ecotourism potential of Panorama Lereng Semeru can be developed optimally.